2010
DOI: 10.1111/j.1365-2710.2010.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health services use following the initiation of risperidone long-acting therapy among schizophrenia patients in the veterans health administration

Abstract: Despite the values of RLAT in treating patients with schizophrenia, RLAT is largely underutilized in routine clinical practice. This observation highlights the importance for future research to ascertain the cost-effectiveness of initiating RLAT, especially the extent to which medication adherence influences the prescription pattern of RLAT and subsequent costs of initiating RLAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Consistent with the findings of the current study, the existing literature includes reports of the efficacy of PP with respect to reducing hospitalization rates and costs in patients with schizophrenia compared to placebo [17] and OAT medications [4,10,18]; one of those studies involved a within-patients comparison [9,19]. Our results are consistent with prior findings that once-monthly administration of PP enhances treatment adherence, ultimately reducing the economic burden associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings of the current study, the existing literature includes reports of the efficacy of PP with respect to reducing hospitalization rates and costs in patients with schizophrenia compared to placebo [17] and OAT medications [4,10,18]; one of those studies involved a within-patients comparison [9,19]. Our results are consistent with prior findings that once-monthly administration of PP enhances treatment adherence, ultimately reducing the economic burden associated with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous 12-week study, patients with schizophrenia showed improved symptoms and reduced side effects, such as extrapyramidal symptoms, when previous OAT medications were replaced with LAIs, regardless of the type of OAT medication [20]. Similarly, previous studies have demonstrated that patients treated with LAIs made more outpatient visits, for regular administration of injections [19] and because of their transition to outpatient treatment following early discharge from the hospital [14].…”
Section: Discussionmentioning
confidence: 92%
“…Ren et al studied patients who initiated LAIs in a Veterans Administration clinic for psychiatric outpatient visits and hospitalizations. 31 Among 924 patients, the number of psychiatric-related outpatient visits increased from 24.6 to 39.1 ( P <0.001), the number of psychiatric hospitalizations decreased from 1.4 to 1.0 ( P <0.001), and the average inpatient length of stay was reduced from 20 to 14 days ( P <0.001). The proportion of patients who experienced at least one psychiatric-related hospitalization decreased from 68.9% to 45.7% ( P <0.001), and the proportion with two hospitalizations decreased from 34.9% to 24.4% ( P <0.001).…”
Section: Lais and Schizophrenia Outcomesmentioning
confidence: 98%
“… 2) Indeed, several studies have demonstrated that LAI antipsychotics may maintain medication adherence and prevent relapse. 11 16) However, the majority of psychiatrists use LAI antipsychotics very conservatively, particularly in Asian countries. 17 , 18) …”
Section: Main Subjectsmentioning
confidence: 99%